Impact of foliar application of plant growth regulators and nutrients on high temperature stress mitigation in rice (oryza stavia L) - Raghunath M P (Department of Plant Physiology, College of Agriculture, 2019)
The study entitled “Impact of foliar application of plant growth regulators and nutrients on high temperature stress mitigation in rice (Oryza sativa L.)” was conducted in the Department of Plant Physiology, College of Agriculture, Vellayani during August to December of 2018 with the objectives to study the effect of foliar application of plant growth regulators and nutrients on high temperature mitigation and to advance the flowering time by using methyl jasmonate (MeJA) in rice.